Prawna i faktyczna sytuacja włoskich Żydów w dobie prześladowań faszystowskich 1938–1943 - Podemski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The paper constitutes the second part of the author’s series of studies on the Jewish question in Fascist Italy written for “Studia nad Autorytaryzmem i Totalitaryzmem.” The author analyses the political context as well as the specific regulations resulting from the breakthrough in Fascist racial policies in 1938. He then comes up with an overview of the new anti-Semitic laws’ troubled practical implementation and gradual extension until 1943. In particular, his attention has been devoted to the debatable reality behind the Fascist slogan: “Discrimination, and not persecution” as well as the complex issue of numerous exceptions and the diversity of ways different categories of Jews were treated by the regime Italian vs. non-Italian Jews, war veterans, families of those fallen for the Fascist cause etc.. Another vital aspect presented is the scholars’ discussion concerning the nature of Italian “concentration” or “internment” camps, meant not exclusively for the Jews, whose identification with Nazi death camps is universally regarded as improper. The final remarks have been dedicated to the variety of attitudes displayed by Italian Jews towards the Fascist state and the Italian masses towards the persecuted Jews, with special emphasis on the deeply embedded Jewish affinity for Italian identity and even Fascist Italy, the passive approach of most Italians and the diversity of views among Italian Catholics.
Keywords: faszyzm; Włochy; Żydzi; prawa antysemickie